2014
DOI: 10.1002/embj.201385887
|View full text |Cite
|
Sign up to set email alerts
|

Bassoon-disruption slows vesicle replenishment and induces homeostatic plasticity at a CNS synapse

Abstract: Endbulb of Held terminals of auditory nerve fibers (ANF) transmit auditory information at hundreds per second to bushy cells (BCs) in the anteroventral cochlear nucleus (AVCN). Here, we studied the structure and function of endbulb synapses in mice that lack the presynaptic scaffold bassoon and exhibit reduced ANF input into the AVCN. Endbulb terminals and active zones were normal in number and vesicle complement. Postsynaptic densities, quantal size and vesicular release probability were increased while vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 85 publications
5
59
0
Order By: Relevance
“…These results demonstrate that the level of sound evoked activity can dramatically alter the excitability at synapses that relays activity between the auditory nerve and the CN. Pre and post-synaptic homeostatic mechanisms similar to this have also been found to modulate synaptic efficiency and gain in several other forms of cochlear hearing loss (Mendoza Schulz et al, 2014; Oleskevich and Walmsley, 2002; Taberner and Liberman, 2005). …”
Section: Discussionmentioning
confidence: 77%
“…These results demonstrate that the level of sound evoked activity can dramatically alter the excitability at synapses that relays activity between the auditory nerve and the CN. Pre and post-synaptic homeostatic mechanisms similar to this have also been found to modulate synaptic efficiency and gain in several other forms of cochlear hearing loss (Mendoza Schulz et al, 2014; Oleskevich and Walmsley, 2002; Taberner and Liberman, 2005). …”
Section: Discussionmentioning
confidence: 77%
“…Additionally, since the present study focused on the effects of CHL in A1, we cannot exclude whether synaptic scaling or other homeostatic mechanisms take place at lower-order stages of the auditory pathway, which is, however, discussed controversially 16,46 . We found that the suppressive effect of salient sound evoked A1 responses on visually driven V1 activity was precisely restored along with TNFα dependent A1 homeostasis (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…; Mendoza Schulz et al . ). We investigated STD in response to AP‐trains applied at 100 Hz (50 stimuli).…”
Section: Resultsmentioning
confidence: 97%
“…; Mendoza Schulz et al . ). We determined the replenishment rate of SVs at the AZ and the RRP size using the cumulative EPSC analysis of 100 Hz AP‐trains.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation